Simultaneous endovascular treatment of synchronous symptomatic acute type B aortic dissection and large infrarenal aortic aneurysm. Technical tips and case report. (2020) - Dinoto, Ettore; Pecoraro, Felice; Farina, Arduino; Viscardi, Alessia; Bajardi, Guido
Highlights: Acute type B aortic dissection associated with AAA, has a high rupture risk. This complicated dissection must be considered for treatment as quickly. This approach can be performed endovascularly when supraaortic trunks are involved. Totally endovascular solution to address both disease is feasible. Abstract: Introduction: Data from the literature suggest that in patients with acute type B aortic dissection (ATBAD), associated with AAA, rupture risk is higher at the confluence tract than isolated lessions. Herein, we report a case of ATBAD and AAA managed with simultaneous intervention. Case presentation: We report a complicated case of a symptomatic patient presenting with a type B aortic dissection and false lumen extension into superior mesenteric artery (SMA) with an infrarenal abdominal aortic aneurysm (AAA). Severe back pain and hypertension were the patient's initial complaints. This patient underwent endovascular repair with a thoracic and infrarenal aortic endograft. Discussion: AAA rupture has been detected at admission in three-fourths of patients with ATBAD that extended to or involved a coexisting unoperated atherosclerotic aneurysms. Prompt surgical intervention is essential to deal with this dreadful aortic emergency. Conclusion: In our experience a totally endovascular solution to treat a complicated ATBAD plus AAA was a rapid solution with low invasivity, no complication and complete healing of patients.